TINJAUAN YURIDIS TENTANG PENYELESAIAN SENGKETA PERBANKAN MELALUI LEMBAGA MEDIASI - Muhammad Alif Putra Ramadhan (JURNAL ILMU HUKUM TOPOSANTARO, 2025)
This research aims to find out the process of legalizing children outside of marriage as legal children and to find out the legal consequences that arise with the recognition and legalization of children outside of marriage. The result of this study is that the process of legalizing an extra-marital child as a legitimate child is initiated through a court decision by submitting an application to the local District Court accompanied by supporting evidence and paying a sum of money for the case fee, then recording the legalization of an extra-marital child to Disdukcapil then the resulting product is that on the child’s birth certificate at the back there will be a marginal note that says the child has a biological father based on a child legalization decision from the court and obtains a child legalization certificate. The legal consequences arising from the recognition and ratification of children outside of marriage are the same as children born in a legal marriage, as long as their biological father can be proven by valid evidence according to law. Penelitian ini bertujuan untuk mengetahui peroses pengesahan anak luar kawin sebagai anak sah dan untuk mengetahui akibat hukum yang timbul dengan adanya pengakuan dan pengesahan anak diluar kawin. Metode yang digunakan pada penelitian adalah yuridis normative.Hasil penelitian ini yaitu proses pengesahan anak luar kawin sebagai anak sah adalah diawali melalui penetapan pengadilan dengan mengajukan permohonan ke Pengadilan Negeri setempat disertai dengan bukti-bukti pendukung dan membayar sejumlah uang untuk panjar biaya perkara, selanjutnya pencatatan pengesahan anak luar kawin ke Disdukcapil lalu produk yang dihasilkan yaitu pada akta kelahiran anak dibagian belakang akan ada catatan pinggir yang tertulis anak tersebut memiliki ayah biologis berdasarkan putusan pengesahan anak dari pengadilan dan mendapatkan akta pengesahan anak. Akibat hukum yang timbul dengan adnya pengakuan dan pengesahan anak diluar kawin maka kedudukan anak luar kawin sama dengan anak yang lahir di dalam perkawinan yang sah, sepanjang ayah biologisnya dapat dibuktikan dengan alat bukti yang sah menurut hukum.